Landscape‐scale variation in an anthropogenic factor shapes immune gene variation within a wild population. Issue 17 (10th August 2016) - Gonzalez‐Quevedo, Catalina; Davies, Richard G.; Phillips, Karl P.; Spurgin, Lewis G.; Richardson, David S.
Abstract: Understanding the spatial scale at which selection acts upon adaptive genetic variation in natural populations is fundamental to our understanding of evolutionary ecology, and has important ramifications for conservation. The environmental factors to which individuals of a population are exposed can vary at fine spatial scales, potentially generating localized patterns of adaptation. Here, we compared patterns of neutral and major histocompatibility complex (MHC) variation within an island population of Berthelot's pipit ( Anthus berthelotii ) to assess whether landscape‐level differences in pathogen‐mediated selection generate fine‐scale spatial structuring in these immune genes. Specifically, we tested for spatial associations between the distribution of avian malaria, and the factors previously shown to influence that distribution, and MHC variation within resident individuals. Although we found no overall genetic structure across the population for either neutral or MHC loci, we did find localized associations between environmental factors and MHC variation. One MHC class I allele (ANBE48) was directly associated with malaria infection risk, while the presence of the ANBE48 and ANBE38 alleles within individuals correlated (positively and negatively, respectively) with distance to the nearest poultry farm, an anthropogenic factor previously shown to be an important determinant of disease distribution in the study population. Our findings highlight the importance of considering small spatial scales when studying the patterns and processes involved in evolution at adaptive loci.